2019
DOI: 10.1097/ajp.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Long-term Risk of Recurrence After Percutaneous Radiofrequency Thermocoagulation of the Gasserian Ganglion for Patients With Trigeminal Neuralgia

Abstract: Objective: This study aimed to estimate risk factors associated with recurrence after radiofrequency thermocoagulation (RFT) of the Gasserian ganglion among a large sample of patients with trigeminal neuralgia (TN) during a long-term follow-up. Materials and Methods: We performed a multicenter retrospective analysis of data from 1481 patients with TN who underwent RFT from 2005 through 2017. Recurrence-free survival (RFS) was assessed by the Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
4
20
1
Order By: Relevance
“…The recurrence rate was 29% with a 14‐year follow‐up period. Compared with our previous research, the recurrence rate was lower than that with RFT for patients with TN 3 . The other reported recurrence rate for TN with isolated or concomitant V1 division was 30% to 60% after RFT, and no correlation was found with RFT temperature, which was consistent with our findings 16 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The recurrence rate was 29% with a 14‐year follow‐up period. Compared with our previous research, the recurrence rate was lower than that with RFT for patients with TN 3 . The other reported recurrence rate for TN with isolated or concomitant V1 division was 30% to 60% after RFT, and no correlation was found with RFT temperature, which was consistent with our findings 16 .…”
Section: Discussionsupporting
confidence: 89%
“…BNI class II facial hypesthesia could result from long‐term medication and a history of at least 2 past neurosurgeries that caused nerve damage due to the operation 25 . These risk factors were consistent with our previous report, and the highest HR was for the previous history of neurosurgeries 3,26 . For further study, the pathophysiological changes of recurrent TN were especially important and should be considered.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite the slightly lower remission rate in coblation group, there was no statistically signi cant difference. Some literature review reported that the remission rate after RFT 22,24 ranged from 50.4-80.7% in a follow-up of 5 years. However, as a relatively novel technique for the treatment of ITN, it was di cult to perform the long-term results according to the available and limited clinical data.…”
Section: Discussionmentioning
confidence: 99%